Religiosity as Moderator of Stress and Well-being among Muslim Students During the Pandemic in Indonesia - Nurussakinah Daulay; Nefi Darmayanti; Ade Chita Putri Harahap; Sri Wahyuni; Rina Mirza; Salamiah Sari Dewi; Suryani Hardjo; Yudistira Fauzy Indrawan; Siti Aisyah; Dinda Permatasari Harahap; Munisa Munisa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2022)
This study aimed to examine the effect of stress and religiosity on well-being and the role of religiosity in moderating the relationship between stress and well-being during the COVID-19 pandemic. This study involved 1233 Indonesian Muslim students from whom data were collected through a survey by distributing questionnaires online. Data collection was made through surveys by distributing online questionnaires in Bahasa, including The Depression Anxiety Stress Scale-21 (DASS-21), the Short Muslim Belief and Practice Scale (Short-MPBS), and The Warwick-Edinburgh Mental Well-being Scale (WEMWBS). The data analyses included bivariate correlation, multiple regression, and moderated regression analyses. The results showed: 1) There was a negative relationship between stress and religiosity and well-being; 2) There was an effect of stress and religiosity together on well-being; 3) Religiosity moderated the relationship between stress and well-being, which means that the hypotheses were supported by the data. The implication of this study is to strengthen positive psychological theory that various factors that previously could cause anxiety and stress in students do not have a bad impact on causing misery, because religiosity can provide reinforcement so that their welfare is maintained in the midst of difficult conditions.